2004
DOI: 10.2134/jeq2004.0956
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Crown Condition in Eucalypt Vegetation by Remotely Sensed Optical Indices

Abstract: Leaf and crown damage and discoloration characteristics are important variables when defining the health of eucalypt tree species and have been used as key indicators of environmental quality. These indicators can vary significantly over a few hectares, especially in mixed-species forests, making field-based environmental surveillance of crown condition an extremely expensive and logistically impractical task. Reflectance in narrow spectral wavelengths obtained from a field-based spectroradiometer and a Compac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 52 publications
1
27
0
3
Order By: Relevance
“…It had a significant and strong relationship with percentage total leaf cover for E. grandis (table 4) but not for E. pilularis (table 3). Coops et al (2004) found that the slope of the total red edge was more strongly correlated to crown density than the lower red edge slope for some native eucalypt species, to a degree which is similar to results found here with E. grandis for correlation with total leaf cover (table 4). In our study of E. pilularis the lower red edge slope was not significantly different for stressed and healthy plants nor was it correlated to the percentage leaf cover data (table 3).…”
Section: Comparison Of Healthy and Stressed (Discoloured) E Grandis supporting
confidence: 86%
See 1 more Smart Citation
“…It had a significant and strong relationship with percentage total leaf cover for E. grandis (table 4) but not for E. pilularis (table 3). Coops et al (2004) found that the slope of the total red edge was more strongly correlated to crown density than the lower red edge slope for some native eucalypt species, to a degree which is similar to results found here with E. grandis for correlation with total leaf cover (table 4). In our study of E. pilularis the lower red edge slope was not significantly different for stressed and healthy plants nor was it correlated to the percentage leaf cover data (table 3).…”
Section: Comparison Of Healthy and Stressed (Discoloured) E Grandis supporting
confidence: 86%
“…Curran (1990) found no relationship between the red edge and chlorophyll content of whole canopies, due to the influence of understorey vegetation. However, Coops et al (2004) found that the RE T and RE ls were well correlated with crown density when individual tree crowns were delineated in high resolution imagery and the reflectance data extracted for analysis. This agrees with results found here for E. globulus as the RE ls and RE T were very strongly correlated with leaf cover, as was the REP.…”
Section: Effect Of Defoliation Pattern For E Globulusmentioning
confidence: 95%
“…That is, leaf reflectance profiles acquired with hand spectrometers or ground-based hyperspectral imaging cameras may vary from those obtained with airborne remote sensing systems (24,53,130,151). Such differences are attributed to a range of factors, including atmosphere, shadow pattern, background composition, and instrument noise (24).…”
Section: Spectral Repeatability Of Reflectance Datamentioning
confidence: 99%
“…Numerous methods have been used to classify entomological remote sensing data, including analysis of reflectance values of single spectral bands (93,98), spectral band indices (17,24,79,85,90,95), partial least square (PLS) (2,4,63), principal component analysis (PCA) (90,102), linear discriminant analysis (LDA) (94), decision trees (37), neural network (73), support vector machine (SVM) (111), variogram analysis (90-93, 95, 97, 100), and spatial pattern analysis (5-7). Sometimes reflectance values of spectral bands are transformed prior to classification, and the most common transformations include conversions of reflectance profiles into first-or second-order derivatives (26).…”
Section: Classification Of Remote Sensing Datamentioning
confidence: 99%
“…[15][16][17] Land Monitor II, a Landsat-based vegetation trend product has been demonstrated to be useful in monitoring vegetation changes over time. 18,19 However, the spatial resolution (30 m) of the Landsat Thematic Mapper (TM) sensor limits the capacity to detect individual tree crowns and in-crown foliage variability.…”
Section: Introductionmentioning
confidence: 99%